Closing the pneumococcal conjugate vaccine (PCV) introduction gap: an archetype analysis of last-mile countries - Preetika Banerjee; Jasmine Huber; Veronica Denti; Molly Sauer; Rose Weeks; Baldeep K. Dhaliwal; Anita Shet (Taylor & Francis Group, 2023)
Background Pneumonia remains the leading infectious cause of global childhood deaths, despite the availability of pneumococcal conjugate vaccine (PCV) products and widespread evidence of their safety and efficacy. Objective To map the landscape of countries that are yet to fully include PCV in their National Immunization Programs, we conducted an archetype analysis of country indicators related to barriers and facilitators for PCV decision-making. Methods We created a country matrix focused on three key domains - health characteristics, immunisation factors, and policy framework, and identified ten related indicators. We scored countries based on indicator performance and subsequently ranked and grouped them into three archetypes of low-, moderate-, and high-barrier countries with regard to PCV introduction. Results Our results indicated 39 countries (33 low- and middle-income countries [LMICs] and 6 high-income countries) that are yet to introduce PCV. Among LMICs, 15 countries were classified as 'low-barrier,' indicating factors favourable for PCV introduction such as high immunisation coverage of common childhood vaccines, supportive governments, and substantial disease burden and eligibility for Gavi support. Countries classified in the 'moderate-barrier' (12) and 'high-barrier' (6) archetypes demonstrated adequate capacity in immunisation systems but had competing national priorities and cost barriers that impeded policy decision-making on PCV introduction. Conclusions The current health and policy indicator-based categorisation provides an actionable framework to design tailored PCV advocacy within these last-mile countries. Policy approaches emerging from this framework can lead to strengthened decision-making on vaccine introduction and sustained vaccine access that can enhance child survival worldwide.